Giving Some Concentrations of Ethephon on The Growth and Yield of Watermelon (Citrullus Lanatus (Thunb.) Matsum. & Nakai.) - Novita Hera; Yudi Krisnawan; Ervina Aryanti (Jurnal Biologi Tropis, 2023)
Watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai.) is one of the horticultural commodities that have a fairly high economic value. Watermelon plants are more dominant in producing male flowers than female flowers. Therefore it is necessary to be able to change the sexual expression of watermelon flowers. One of the efforts that can be made to increase production watermelon is by administering the growth regulating agent ethepon. This study aims to find the best concentration of ethepon on watermelon growth and yield. This study used a randomized block design (RBD) consisting of 5 treatments and repeated 4 times. The treatment given was giving the concentration of ethepon which consisted of 5 levels, namely control (0 ppm), 100 ppm, 200 ppm, 300 ppm and 400 ppm. The parameters observed were plant length, number of leaves, when the first male flower appeared, when the first female flower appeared, the number of male flowers, the number of female flowers, the number of fruit planted, the weight of fruit planted and the length of the fruit. The results of research that have been carried out show that the application of ethepon with a concentration of 100 ppm is the best concentration in increasing when the first male flowers appear, the number of male flowers, the number of female flowers, the number of fruits per plant and the weight of fruit per plant.